CONTRADICTORY CHARACTER TRAITS AS SEEN IN PERSONA 4: THE ANIMATION - Nathasa Ayu Sabrina; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2015)
Anime is Japanese cartoon that has a vast popularity due to its story and art. The popularity of anime results in the various genres such as: crime-fiction, urban fantasy, and slice of life. One of the popular animes that combines the three genres is Persona 4: the Animation. The popularity and the combination of three genres of that anime makes me interested in analyzing this anime. I am particularly attracted to the two main characters in Persona 4: The Animation namely, Yu Narukami and Tohru Adachi. Those two main character possess contradictory character traits and represent a certain symbol on the society. In this paper, I examine the values that influence their character traits. Using Carl Gustav Jung’s theory of individuation, I proves that they have contradictory character traits by looking through their Persona, Shadow, Ego, and Self. Through the analysis of character traits, I find that they symbolize yin yang. Like yin yang, they are contradicting as well as complementing. Yet, they also are not paragon of evil or good